PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN PERSEPSI LINGKUNGAN KERJA SEBAGAI VARIABEL INTERVENING PADA PDAM KABUPATEN BENGKALIS - Arrabban Arif; Marzolina Marzolina; Marhadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted at Bengkalis Regency PDAM with the aim to discuss Work Discipline and Motivation on Employee Performance with the Perception of Work Environment as Intervening Variable in Bengkalis Regency PDAM. Type of quantitative descriptive research. The population in this study were employees of PDAM Bengkalis Regency. The sampling technique used census techniques. Participation was taken as many as 58 employees of Bengkalis Regency PDAM. The technique of collecting data with questionnaires. The method of multiple linear regression analysis using SPSS version 20. The results of the evaluation conducted on work discipline, a significant motivation for the performance of PDAM employees in Bengkalis Regency. Work discipline, motivation significantly influence the perception of the work environment. Discipline and motivation have a significant effect on perception of the work environment and performance. Work environment perception on performance.Keywords: Discipline, Motivation, Perception of Work Environment, Performance